2014
DOI: 10.1074/mcp.m113.036632
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Antidisease Immunity Using Proteome Arrays and Sera from Children Naturally Exposed to Malaria

Abstract: Malaria remains one of the most prevalent and lethal human infectious diseases worldwide. A comprehensive characterization of antibody responses to blood stage malaria is essential to support the development of future vaccines, sero-diagnostic tests, and sero-surveillance methods. We constructed a proteome array containing 4441 recombinant proteins expressed by the blood stages of the two most common human malaria parasites, P. falciparum (Pf) and P. vivax (Pv), and used this array to screen sera of Papua New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 84 publications
2
30
0
Order By: Relevance
“…This methodology generates a multitude of decision trees and measures the mean decrease in classifier accuracy (MDCA) when a particular feature (e.g., transcript level detected by a var primer) is removed from the model. Recent advances in computational techniques have made it possible to associate P values with features ranked in this manner (40,41). First, we used a RF (39) with 1,000,000 trees to select parasite features that could be used to accurately predict patient hospitalization and disease severity.…”
Section: Resultsmentioning
confidence: 99%
“…This methodology generates a multitude of decision trees and measures the mean decrease in classifier accuracy (MDCA) when a particular feature (e.g., transcript level detected by a var primer) is removed from the model. Recent advances in computational techniques have made it possible to associate P values with features ranked in this manner (40,41). First, we used a RF (39) with 1,000,000 trees to select parasite features that could be used to accurately predict patient hospitalization and disease severity.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore 1,949 P. vivax recombinant proteins (87%) were expressed with at least one tag suggesting that these recombinant proteins were at least partially expressed. 22 Microarray data analysis. A reactive protein was defined as a protein that had a signal intensity values > 2-fold the mean of the "no DNA" intensity values for the same sample (i.e., column on the matrix) in at least 10% of the samples in the Pv-infected group, Pv reinfected group or the Pv relapse group.…”
Section: Ethicsmentioning
confidence: 99%
“…A proteome array was designed containing 2,233 P. vivax recombinant proteins, representing 1,936 predicted P. vivax asexual blood-stage proteins and comprised as recently described. 22 Proteins predicted to be secreted or present on the parasite surface, on the basis of the presence of a secretory signal peptide or transmembrane domains, were annotated as such in PlasmoDB 34,35 and preferentially included. Additional selection for expression of P. vivax genes included expression microarray evidence for blood-stage expression.…”
Section: Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[42] Finally, a protein microarray with 1963 P. vivax proteins expressed in a cell-free Escherichia coli in vitro transcription–translation system were used to study host responses in symptomatic children and asymptomatic children who were diagnosed as positive for P. vivax but were not febrile. [43] This report suggested that a wider range of serological responses to P. vivax proteins in asymptomatic children could perhaps provide protection. A recent report that used 515 P. vivax proteins to probe 353 plasma samples from Indian patients also identified immunogenic antigens.…”
Section: Proteomics Studies Have Started To Address Some Of the Gamentioning
confidence: 99%